Size-Specific Particulate Matter Associated With Acute Lower Respiratory Infection Outpatient Visits in Children: A Counterfactual Analysis in Guangzhou, China - Liang, Zhenyu; Meng, Qiong; Yang, Qiaohuan; Chen, Na; You, Chuming (Frontiers in Public Health, 2021)
The burden of lower respiratory infections is primarily evident in the developing countries. However, the association between size-specific particulate matter and acute lower respiratory infection (ALRI) outpatient visits in the developing countries has been less studied. We obtained data on ALRI outpatient visits (N = 105,639) from a tertiary hospital in Guangzhou, China between 2013 and 2019. Over-dispersed generalized additive Poisson models were employed to evaluate the excess risk (ER) associated with the size-specific particulate matter, such as inhalable particulate matter (PM10), coarse particulate matter (PMc), and fine particulate matter (PM2.5). Counterfactual analyses were used to examine the potential percent reduction of ALRI outpatient visits if the levels of air pollution recommended by the WHO were followed. There were 35,310 pneumonia, 68,218 bronchiolitis, and 2,111 asthma outpatient visits included. Each 10 μg/m3 increase of 3-day moving averages of particulate matter was associated with a significant ER (95% CI) of outpatient visits of pneumonia (PM2.5: 3.71% [2.91, 4.52%]; PMc: 9.19% [6.94, 11.49%]; PM10: 4.36% [3.21, 5.52%]), bronchiolitis (PM2.5: 3.21% [2.49, 3.93%]; PMc: 9.13% [7.09, 11.21%]; PM10: 3.12% [2.10, 4.15%]), and asthma (PM2.5: 3.45% [1.18, 5.78%]; PMc: 11.69% [4.45, 19.43%]; PM10: 3.33% [0.26, 6.49%]). The association between particulate matter and pneumonia outpatient visits was more evident in men patients and in the cold seasons. Counterfactual analyses showed that PM2.5 was associated with a larger potential decline of ALRI outpatient visits compared with PMc and PM10 (pneumonia: 11.07%, 95% CI: [7.99, 14.30%]; bronchiolitis: 6.30% [4.17, 8.53%]; asthma: 8.14% [2.65, 14.33%]) if the air pollutants were diminished to the level of the reference guidelines. In conclusion, short-term exposures to PM2.5, PMc, and PM10 are associated with ALRI outpatient visits, and PM2.5 is associated with the highest potential decline in outpatient visits if it could be reduced to the levels recommended by the WHO.